Success in Two Languages: An Analysis of the Passing Rate of Texas Bilingual Teachers - Freeman, Lynn S; Lin, Hsin-Hui; Tsao, Ling-Ling (International Journal of Asian Social Science, 2012)
This study analyzed the competency of bilingual teachers as it pertains to the passage of the TExEs Content Exam. Texas is in a state of transition; not only are its’ certification requirements changing, from EC-4 to EC-6, but its’ population continues to change, creating an increasingly diverse student body. There are multiple issues that educators and teacher certification entities must address, among them: to continue to identify and implement strategies to educate a very heterogeneous k-12 population of students, and how to prepare teachers to face these challenges. This study represents one of the last comprehensive analyses of teacher success under the former TEA certification guidelines. It can therefore serve as a basis of comparison for the passing rates of teachers in the fall of 2010 and beyond, when the state phases out previous bilingual and supplemental exams EC-4 and 4-8 exams, and offers the TExES Bilingual Education Supplemental Exam (164) and the TExES Bilingual Generalist Exam (192). With the accountability standards imposed by NCLB, the “highly qualified” teachers are determined by the results of standardized tests. The results of this study may guide policy makers when seek solutions to improve school bilingual teacher preparation by determining the areas in which effort and support is most needed.